A graphene / polydimethylsiloxane composite aerogel and its preparation method and application
The preparation of graphene/polydimethylsiloxane composite aerogels by the Pickering emulsion method solved the problems of insufficient structural stability and poor mechanical strength of existing graphene aerogels, and achieved the improvement of the mechanical properties and application expansion of the material.
Patent Information
- Application Number
- CN202310132150.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-20
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-02-20
AI Technical Summary
The existing graphene aerogels have insufficient structural stability and poor mechanical strength during mechanical circulation and cutting processing, which lead to easy breakage and disintegration, which limits their practical application.
Graphene oxide was mixed with polydimethylsiloxane prepolymer by Pickering emulsion method, and subjected to non-directional freezing, freeze-drying and thermal curing to form graphene/polydimethylsiloxane composite aerogel, which used the bonding and toughening effects of PDMS to enhance the mechanical properties of the material.
The prepared graphene/polydimethylsiloxane composite aerogel has excellent mechanical strength, flexibility and processability, can undergo high strain compression in the three-dimensional direction, and displays good fatigue resistance and hydrophobicity.
Smart Images

Figure CN116355271B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of graphene aerogel materials, and in particular to a graphene / polydimethylsiloxane composite aerogel and a preparation method and application thereof. Background Art
[0002] Graphene oxide (GO) has excellent gel ability and good water solubility, and it is easy to use template molding or induced assembly to obtain graphene aerogel (GA) with excellent mechanical and electrical properties, thus showing strong production and application potential. However, 3DGA assembled using GO, although it has properties such as high elasticity and high conductivity, also has disadvantages such as insufficient structural stability and poor mechanical strength. It is easy to break or disintegrate during mechanical cycles and cutting processes, which seriously restricts its practicality. This is mainly due to the weak adhesion and interfacial interaction between graphene nanosheets in the 3D skeleton structure, which is easy to produce irreversible damage during compression or deformation by external force. In addition, GA is often prone to significant plastic deformation or shows low compressive strength, which limits its further application.
[0003] In order to improve the flexibility and structural stability of GA, in addition to regulating the internal structure of the aerogel, other materials need to be introduced for reinforcement to achieve certain specific functions. For mechanically loaded fragile materials, the flexibility of the composite material system can be effectively improved by introducing flexible materials such as polymers. Studies have shown that the introduction of polymers such as waterborne polyurethane and polyimide into GA will indeed improve its final mechanical stability. However, directly introducing polymers into the reaction system during the preparation process will affect the assembly behavior and porous structure of GA, which may lead to pore collapse, local agglomeration and even volume shrinkage, which in turn causes the mechanical properties of the modified GA to fail to meet the expected goals.
[0004] Polydimethylsiloxane (PDMS) is widely used in flexible electronic devices due to its good flexibility, resilience, biocompatibility and wide range of thermal stability. The mechanical properties, processing properties and packaging properties of GA can be improved by introducing PDMS into the interior of GA. However, since PDMS is a hydrophobic polymer, it is difficult to dissolve directly in GO aqueous solution for in-situ assembly. For this reason, many researchers use the impregnation method to fill the PDMS molecular chain into the molded GA material to obtain GA / PDMS composite materials. For example, Song et al. (SONGP, LIUB, LIANGC, et al. Lightweight, Flexible Cellulose-Derived Carbon Aerogel@Reduced Graphene Oxide / Pdms CompositeswithOutstandingEmiShieldingPerformancesandExcellentThermalConductivities[J].Nano-MicroLetters, 2021, 13(1):91.) used cellulose and GO to obtain a composite aerogel, and then immersed PDMS in it to obtain a composite material with excellent electromagnetic shielding performance. However, this strategy can only coat PDMS on the pore wall surface of the large pore part of the GA skeleton. The polymer chain is difficult to penetrate into the relatively dense pore wall of GA, and the bonding, toughening and strengthening effects of PDMS cannot be fully exerted. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a graphene / polydimethylsiloxane composite aerogel and a preparation method and application thereof. The present invention realizes the microscopic composite of polydimethylsiloxane and graphene phases, and the prepared graphene / polydimethylsiloxane composite aerogel has excellent mechanical strength, flexibility and processability.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a graphene / polydimethylsiloxane composite aerogel, comprising the following steps:
[0008] Mixing a polydimethylsiloxane prepolymer, a curing agent, an emulsifier and an organic solvent to obtain a polydimethylsiloxane prepolymer solution;
[0009] The graphene oxide aqueous dispersion and the polydimethylsiloxane prepolymer solution are mixed and emulsified to obtain an oil-in-water Pickering emulsion;
[0010] The oil-in-water Pickering emulsion is subjected to random freezing, freeze drying and thermal curing in sequence to obtain a graphene oxide / polydimethylsiloxane composite aerogel;
[0011] The graphene oxide / polydimethylsiloxane composite aerogel is reduced to obtain the graphene / polydimethylsiloxane composite aerogel.
[0012] Preferably, the emulsifier is a Span series emulsifier; the organic solvent includes one or more of cyclohexane, toluene, dichloromethane, chloroform and n-hexane.
[0013] Preferably, the volume ratio of the graphene oxide aqueous dispersion to the polydimethylsiloxane solution is 10:1 to 1:5; the mass concentration of the graphene oxide aqueous dispersion is 0.1 to 5%; the mass ratio of graphene oxide to polydimethylsiloxane prepolymer in the graphene oxide aqueous dispersion is 1:1 to 1:100; the mass ratio of graphene oxide to emulsifier in the graphene oxide aqueous dispersion is 1:0.1 to 1:5.
[0014] Preferably, the emulsification is carried out in a high-speed emulsifier, the rotation speed of the emulsification is 500 to 9000 rpm, and the time is 3 to 15 minutes.
[0015] Preferably, the temperature of the non-directional freezing is -10 to -200°C, and the time is more than 5 hours.
[0016] Preferably, the freeze-drying temperature is 0 to -80°C, and the freeze-drying time is more than 24 hours.
[0017] Preferably, the thermal curing temperature is 20 to 250° C. and the time is 0.1 to 48 hours.
[0018] Preferably, the reduction is carried out in the presence of a reducing agent, which includes one or more of hydrazine hydrate, sodium borohydride, ethylenediamine, ascorbic acid and thiourea dioxide; the reduction temperature is 20 to 200° C. and the time is 0.5 to 24 hours.
[0019] The present invention provides a graphene / polydimethylsiloxane composite aerogel prepared by the preparation method described in the above technical solution, and the graphene / polydimethylsiloxane composite aerogel has isotropy.
[0020] The present invention provides the application of the graphene / polydimethylsiloxane composite aerogel described in the above technical solution in the field of flexible sensor devices and oil-water separation.
[0021] The invention provides a method for preparing a graphene / polydimethylsiloxane composite aerogel, comprising the following steps: mixing a polydimethylsiloxane (PDMS) prepolymer, a curing agent, an emulsifier and an organic solvent to obtain a polydimethylsiloxane prepolymer solution; mixing a graphene oxide (GO) aqueous dispersion with the polydimethylsiloxane prepolymer solution for emulsification to obtain an oil-in-water Pickering emulsion; subjecting the oil-in-water Pickering emulsion to random freezing, freeze drying and thermal curing in sequence to obtain a graphene oxide / polydimethylsiloxane composite aerogel; and reducing the graphene oxide / polydimethylsiloxane composite aerogel to obtain a graphene / polydimethylsiloxane composite aerogel. The present invention uses the Pickering emulsion method to compound GO (hard) nanosheets with excellent water solubility with oil phase PDMS (soft), and uses GO as a stabilizer to prepare a water-in-oil (O / W) emulsion with good stability. This method solves the problem of compounding oily polymer soft chains and water-soluble hard GO nanosheets on the one hand; on the other hand, PDMS is in situ adhered to the GO nanosheets as an interface enhancement medium, and then GO is self-crosslinked to form a composite skeleton structure, so that the prepared aerogel has good flexibility and elasticity; in addition, the present invention uses non-directional freezing to make the ice particles in the emulsion crystallize uniformly in all directions to obtain an isotropic porous structure, so that the material has mechanical isotropy. After that, water and excess oil phase (organic solvent) are removed by freeze drying, and GO is reduced to obtain a good GA structure. The present invention adopts the above-mentioned in-situ combination preparation strategy to obtain a "soft-hard" phase micro-composite aerogel material of hydrophobic PDMS and hydrophilic GO, fully realizing the good synergistic effect between the flexibility of PDMS and the strength of graphene nanosheets. The obtained aerogel material has an isotropic structure and has strong compressive resistance, fatigue resistance, superelasticity, good processability and flexibility.
[0022] The present invention provides a graphene / polydimethylsiloxane composite aerogel prepared by the preparation method described in the above technical solution. The results of the embodiment show that the density of the graphene / polydimethylsiloxane composite aerogel provided by the present invention is 12.8-98.5 mg / cm 3, modulus is 2.65~9.23kPa, with compressive strength up to 1.7MPa; excellent fatigue resistance (10,000 cycles at 50% strain); isotropic, can be compressed with high strain (90%) in three-dimensional direction; has good toughness and easy processing, can be cut and processed arbitrarily in three-dimensional direction; and thanks to the hydrophobicity of PDMS, graphene / PDMS composite aerogel has good hydrophobicity, and the water contact angle (WCA) is 124.3~144°. In general, the graphene / PDMS composite aerogel provided by the present invention has excellent mechanical properties, processability and hydrophobicity, and has broad application prospects in the fields of flexible sensor devices and oil-water separation. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 are optical microscope images of the Pickering emulsion prepared in Example 1 at different scales, Figure 1 (a) and (b) correspond to optical microscope images at different magnification scales;
[0024] Figure 2 is a microscopic morphology of the graphene / PDMS composite aerogel prepared in Example 1, Figure 2 (a) and (b) correspond to microscopic morphology images at different magnification scales;
[0025] Figure 3 is the EDS element distribution diagram of the graphene / PDMS composite aerogel prepared in Example 1, Figure 3 (a) to (d) are element analysis diagrams, Si element distribution diagrams, O element distribution diagrams, and C element distribution diagrams of composite aerogels, respectively;
[0026] Figure 4 is a curve showing the stress and stress error of the graphene / PDMS composite aerogel prepared in Example 1 at 50% strain as a function of the number of compression cycles;
[0027] Figure 5 1 is the stress-strain curve of the graphene / PDMS composite aerogel prepared in Example 1 at 10%, 30%, 50%, 70% and 97.5% strain;
[0028] Figure 6 The graphene / PDMS composite aerogel prepared in Example 1 was subjected to three-dimensional (X, Y, Z) compression and non-equilibrium compression. Figure 6 (a) to (f) are respectively the stress-strain diagram of compression in the X direction, the stress-strain diagram of compression in the Y direction, the stress-strain diagram of compression in the Z direction, the scanning electron microscope diagram of compression in the X direction, the scanning electron microscope diagram of compression in the Y direction, the scanning electron microscope diagram of compression in the Z direction, the stress-strain diagram of oblique compression, the stress-strain diagram of transverse compression, and the stress-strain diagram of half-side compression;
[0029] Figure 7 1 is a physical picture of the graphene / PDMS composite aerogel prepared in Example 1 processed into different shapes;
[0030] Figure 8 1 is the stress-strain curve of the graphene oxide / PDMS composite aerogel prepared in Example 6 under different strains (10%, 30%, 50%, 70%, 90%);
[0031] Fig. 9 It is a graph showing the thermal stability test results of the graphene / PDMS composite aerogels prepared in Examples 1 to 5 and graphene (GA) and PDMS. DETAILED DESCRIPTION
[0032] The present invention provides a method for preparing a graphene / polydimethylsiloxane composite aerogel, comprising the following steps:
[0033] Mixing a polydimethylsiloxane prepolymer, a curing agent, an emulsifier and an organic solvent to obtain a polydimethylsiloxane prepolymer solution;
[0034] The graphene oxide aqueous dispersion and the polydimethylsiloxane prepolymer solution are mixed and emulsified to obtain an oil-in-water Pickering emulsion;
[0035] The oil-in-water Pickering emulsion is subjected to random freezing, freeze drying and thermal curing in sequence to obtain a graphene oxide / polydimethylsiloxane composite aerogel;
[0036] The graphene oxide / polydimethylsiloxane composite aerogel is reduced to obtain the graphene / polydimethylsiloxane composite aerogel.
[0037] In the present invention, unless otherwise specified, the raw materials involved are commercially available products well known to those skilled in the art.
[0038] The present invention mixes a polydimethylsiloxane prepolymer, a curing agent, an emulsifier and an organic solvent to obtain a polydimethylsiloxane prepolymer solution. In the present invention, the polydimethylsiloxane prepolymer and the curing agent are preferably component A and component B of Dow Corning 184 PDMS (Dow Corning 184), or preferably component A and component B of Dow Corning 170 PDMS (Dow Corning 170) (Dow Corning 184 PDMS and Dow Corning 170 PDMS are both two-component kit products composed of liquid components, including basic components A and curing agent B, A and B are cured in proportion to obtain polydimethylsiloxane), wherein the mass ratio of component A to component B in Dow Corning 184 PDMS is 10:1, and the mass ratio of component A to component B in Dow Corning 170 PDMS is 1:1. In the present invention, the emulsifier is preferably a Span series emulsifier, more preferably one or more of Span20, Span40, Span60, Span80 and Span85, and further preferably Span60; the organic solvent preferably includes one or more of cyclohexane, toluene, dichloromethane, chloroform and n-hexane, and more preferably cyclohexane. In the present invention, the polydimethylsiloxane prepolymer, curing agent and emulsifier are preferably added to the organic solvent for mixing. The present invention has no special requirements for the mixing method, and it is sufficient to mix the components evenly.
[0039] After obtaining the polydimethylsiloxane prepolymer solution, the present invention mixes the graphene oxide aqueous dispersion with the polydimethylsiloxane prepolymer solution for emulsification to obtain an oil-in-water Pickering emulsion. In the present invention, the graphene oxide used in the graphene oxide aqueous dispersion is prepared using 325 mesh graphite powder as a raw material according to a modified Hummer method; the water used in the graphene oxide aqueous dispersion is preferably deionized water. The present invention has no special requirements for the method for obtaining the graphene oxide aqueous dispersion, and the graphene oxide aqueous dispersion can be obtained by a method well known to those skilled in the art. In the present invention, the volume ratio of the graphene oxide aqueous dispersion to the polydimethylsiloxane solution (i.e., the water-oil volume ratio) is preferably 10:1 to 1:5, more preferably 4:1 to 1:1; the mass concentration of the graphene oxide aqueous dispersion is preferably 0.1 to 5%; the mass ratio of graphene oxide to polydimethylsiloxane prepolymer in the graphene oxide aqueous dispersion is preferably 1:1 to 1:100, more preferably 1:4 to 1:64, and further preferably 1:8 to 1:32; the mass ratio of graphene oxide to emulsifier in the graphene oxide aqueous dispersion is preferably 1:0.1 to 1:5, more preferably 1:0.2 to 1:1. In the present invention, the mixing may be performed by adding the graphene oxide aqueous dispersion to the polydimethylsiloxane prepolymer solution, or by adding the polydimethylsiloxane prepolymer solution to the graphene oxide aqueous dispersion, and the present invention has no special requirements for this. In the present invention, the emulsification is preferably carried out in a high-speed emulsifier, the emulsification speed is preferably 500-9000 rpm, more preferably 1500-5000 rpm, the time is preferably 3-15 min, more preferably 5-10 min. The present invention adopts the Pickering emulsion method, and the water-soluble graphene oxide (GO) is mixed with the oil-soluble polydimethylsiloxane (PDMS) prepolymer, the GO nanosheets are used as a stabilizer, and the PDMS is used as the oil phase to prepare a water-in-oil (O / W) Pickering emulsion with good stability.
[0040] After obtaining the water-in-oil Pickering emulsion, the present invention sequentially performs non-directional freezing, freeze drying and thermal curing on the water-in-oil Pickering emulsion to obtain graphene oxide / polydimethylsiloxane composite aerogel. In the present invention, the specific operation of the non-directional freezing is preferably: the water-in-oil Pickering emulsion is loaded into a mold and placed in a multi-faceted refrigeration cold source, so that it is cooled evenly in all directions, resulting in no directional structure inside. The present invention has no special requirements for the shape of the mold, and it can be set according to actual needs; the present invention has no special requirements for the multi-faceted refrigeration cold source, and it can achieve uniform cooling of the water-in-oil Pickering emulsion. In the present invention, the temperature of the non-directional freezing is preferably -10 to -200°C, more preferably -20 to -50°C, and the time is preferably more than 5h, more preferably 5 to 10h. In an embodiment of the present invention, the non-directional freezing is to load the water-in-oil Pickering emulsion into a mold and place it in a refrigerator at a temperature of -20°C. Because the refrigerator has a large freezing space, directional freezing cannot be produced, so that the emulsion is cooled evenly in all directions. In the present invention, the freeze-drying temperature is preferably 0 to -80°C, more preferably 0 to -50°C, and the freeze-drying time is preferably more than 24 hours, subject to complete drying; the freeze-drying is specifically carried out in a freeze dryer. The present invention uses the non-directional freezing to make the ice particles in the emulsion crystallize uniformly in all directions; the water and excess oil phase (organic solvent) are removed by freeze drying to obtain an isotropic porous structure, thereby achieving mechanical isotropy, so that the final aerogel can be compressed and arbitrarily cut in three-dimensional directions, and the PDMS with good flexibility and adhesion is in situ adhered to the nano GO as an interface enhancement medium, so that the prepared aerogel has good flexibility and elasticity, so that the final aerogel has good toughness and easy processing. In the present invention, the temperature of the thermal curing is preferably 20 to 250° C., more preferably 50 to 150° C., and the time is preferably 0.1 to 48 hours, more preferably 15 to 30 minutes; during the thermal curing process, the polydimethylsiloxane prepolymer and the curing agent undergo a hydrosilylation reaction, and the composite aerogel obtained after freeze-drying can be cured and formed at the thermal curing temperature to form a graphene oxide / polydimethylsiloxane composite aerogel with excellent mechanical properties.
[0041] After obtaining the graphene oxide / polydimethylsiloxane composite aerogel, the present invention reduces the graphene oxide / polydimethylsiloxane composite aerogel to obtain the graphene / polydimethylsiloxane composite aerogel. In the present invention, the reduction is preferably carried out in the presence of a reducing agent, and the reducing agent preferably includes one or more of hydrazine hydrate, sodium borohydride, ethylenediamine, ascorbic acid and thiourea dioxide, more preferably hydrazine hydrate; the reduction temperature is preferably 20 to 200°C, more preferably 50 to 150°C, and the time is preferably 0.5 to 24h, more preferably 5 to 15h. In an embodiment of the present invention, the graphene oxide / polydimethylsiloxane composite aerogel is strongly and quickly reduced with hydrazine hydrate vapor to obtain the graphene / polydimethylsiloxane composite aerogel.
[0042] The present invention adopts the above-mentioned in-situ combination preparation strategy to obtain a "soft-hard" phase micro-composite aerogel material of hydrophobic PDMS and hydrophilic GO, fully realizing the good synergistic effect between the flexibility of PDMS and the strength of graphene nanosheets.
[0043] The present invention provides a graphene / polydimethylsiloxane composite aerogel prepared by the preparation method described in the above technical solution, and the graphene / polydimethylsiloxane composite aerogel has isotropy. The graphene / PDMS composite aerogel provided by the present invention has excellent mechanical properties, processability and hydrophobicity, and has broad application prospects in the fields of flexible sensor devices and oil-water separation.
[0044] The graphene / polydimethylsiloxane composite aerogel provided by the present invention and its preparation method and application are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0045] The PDMS prepolymer and curing agent used in each embodiment are Dow Corning 184 PDMS component A and component B, and the mass ratio of component A to component B is 10:1.
[0046] Example 1
[0047] PDMS prepolymer, curing agent and Span60 are added to cyclohexane to prepare a PDMS prepolymer solution; then a certain concentration of graphene oxide (GO) dispersion is added to the PDMS prepolymer solution, and the water-oil volume ratio is adjusted, and a Pickering emulsion is prepared by emulsifying for 5 minutes using a high-speed emulsifier (rotation speed is 3000rpm); the GO concentration in the Pickering emulsion is 2.5mg / mL, the mass ratio of GO to PDMS prepolymer is 1:16, the mass ratio of GO to Span60 is 5:1, and the volume ratio of GO dispersion to PDMS prepolymer solution (i.e., water-oil volume ratio) is 4:1;
[0048] After stirring, the Pickering emulsion is loaded into a mold and placed in a -20°C refrigerator for freezing for more than 5 hours; the frozen Pickering emulsion is then placed in a freeze dryer for drying for more than 24 hours to remove water and cyclohexane; the dried sample is then taken out and cured at 150°C for 30 minutes to obtain a graphene oxide / PDMS composite aerogel; the thermally cured aerogel is further reduced using hydrazine hydrate vapor at 150°C for 5 hours to obtain a graphene / PDMS composite aerogel.
[0049] Figure 1 are optical microscope images of the Pickering emulsion prepared in Example 1 at different scales, Figure 1 (a) and (b) correspond to optical microscope images at different magnification scales. The Pickering emulsion appears as uniformly dispersed droplets under an optical microscope.
[0050] Figure 2 is a microscopic morphology of the graphene / PDMS composite aerogel prepared in Example 1, Figure 2 (a) and (b) correspond to microscopic morphology images at different magnification scales. Figure 2 The internal structure of the graphene / PDMS composite aerogel is demonstrated, which exhibits a porous network morphology and a solid pore wall structure.
[0051] Figure 3 is the EDS element distribution diagram of the graphene / PDMS composite aerogel prepared in Example 1, Figure 3 (a) to (d) are the element analysis diagram, Si element distribution diagram, O element distribution diagram, and C element distribution diagram of the composite aerogel, respectively. Figure 3 The element distribution inside the graphene / PDMS composite aerogel is demonstrated, proving the uniform distribution of PDMS in the aerogel.
[0052] The density of the graphene / PDMS composite aerogel obtained in Example 1 is about 55.1 mg / cm 3 , modulus of 5.77 kPa, water contact angle of 141.2°, and stress of 3.91 kPa at 50% strain; in addition, the isotropy of the internal structure leads to mechanical isotropy, with the same modulus of 5.77 kPa (error ±0.2 kPa) in the X, Y, and Z directions.
[0053] Example 2
[0054] PDMS prepolymer, curing agent and Span60 were added to cyclohexane to prepare a PDMS prepolymer solution; then a certain concentration of graphene oxide dispersion was added to the PDMS prepolymer solution, and the water-oil volume ratio was adjusted, and a high-speed emulsifier (rotation speed of 3000rpm) was used to emulsify for 5 minutes to prepare a Pickering emulsion; the GO concentration in the Pickering emulsion was 2.5mg / mL, the mass ratio of GO to PDMS prepolymer was 1:4, the mass ratio of GO to Span60 was 5:1, and the water-oil volume ratio was 4:1;
[0055] After stirring, the Pickering emulsion is loaded into a mold and placed in a -20°C refrigerator for freezing for more than 5 hours; the frozen Pickering emulsion is then placed in a freeze dryer for drying for more than 24 hours to remove water and cyclohexane; the dried sample is then taken out and cured at 150°C for 30 minutes to obtain a graphene oxide / PDMS composite aerogel; the thermally cured aerogel is further reduced using hydrazine hydrate vapor at 150°C for 5 hours to obtain a graphene / PDMS composite aerogel.
[0056] The density of the graphene / PDMS composite aerogel obtained in Example 2 is about 12.8 mg / cm 3 , modulus is 2.65 kPa, water contact angle is 124.3°, and stress at 50% strain is 1.38 kPa; in addition, the isotropy of the internal structure leads to mechanical isotropy, with the same modulus of 2.65 kPa (error ± 0.2 kPa) in the X, Y, and Z directions.
[0057] Example 3
[0058] PDMS prepolymer, curing agent and Span60 were added to cyclohexane to prepare PDMS prepolymer solution; then a certain concentration of graphene oxide dispersion was added to the PDMS prepolymer solution, and the water-oil volume ratio was adjusted, and a high-speed emulsifier (rotation speed of 3000rpm) was used to emulsify for 5 minutes to prepare a Pickering emulsion; the GO concentration in the Pickering emulsion was 2.5mg / mL, the mass ratio of GO to PDMS prepolymer was 1:8, the mass ratio of GO to Span60 was 5:1, and the water-oil volume ratio was 4:1;
[0059] After stirring, the Pickering emulsion is loaded into a mold and placed in a -20°C refrigerator for freezing for more than 5 hours; the frozen Pickering emulsion is then placed in a freeze dryer for drying for more than 24 hours to remove water and cyclohexane; the dried sample is then taken out and cured at 150°C for 30 minutes to obtain a graphene oxide / PDMS composite aerogel; the thermally cured aerogel is further reduced using hydrazine hydrate vapor at 150°C for 5 hours to obtain a graphene / PDMS composite aerogel.
[0060] The density of the graphene / PDMS composite aerogel obtained in Example 3 is about 28.1 mg / cm 3 , modulus is 4.9 kPa, water contact angle is 136.3°, and stress at 50% strain is 3.69 kPa; in addition, the isotropy of the internal structure leads to mechanical isotropy, with the same modulus of 4.9 kPa (error ±0.2 kPa) in the X, Y, and Z directions.
[0061] Example 4
[0062] PDMS prepolymer, curing agent and Span60 were added to cyclohexane to prepare PDMS prepolymer solution; then a certain concentration of graphene oxide dispersion was added to the PDMS prepolymer solution, and the water-oil volume ratio was adjusted, and a high-speed emulsifier (rotation speed was 3000rpm) was used to emulsify for 5 minutes to prepare a Pickering emulsion; the GO concentration in the Pickering emulsion was 2.5mg / mL, the mass ratio of GO to PDMS prepolymer was 1:32, the mass ratio of GO to Span60 was 5:1, and the water-oil volume ratio was 4:1;
[0063] After stirring, the Pickering emulsion is loaded into a mold and placed in a -20°C refrigerator for freezing for more than 5 hours; the frozen Pickering emulsion is then placed in a freeze dryer for drying for more than 24 hours to remove water and cyclohexane; the dried sample is then taken out and cured at 150°C for 30 minutes to obtain a graphene oxide / PDMS composite aerogel; the thermally cured aerogel is further reduced using hydrazine hydrate vapor at 150°C for 5 hours to obtain a graphene / PDMS composite aerogel.
[0064] The density of the graphene / PDMS composite aerogel obtained in Example 4 is about 76.3 mg / cm 3 , modulus is 8.93 kPa, water contact angle is 142.0°, and stress at 50% strain is 5.12 kPa; in addition, the isotropy of the internal structure leads to mechanical isotropy, with the same modulus of 8.93 kPa (error ±0.2 kPa) in the X, Y, and Z directions.
[0065] Example 5
[0066] PDMS prepolymer, curing agent and Span60 were added to cyclohexane to prepare PDMS prepolymer solution; then a certain concentration of graphene oxide dispersion was added to the PDMS prepolymer solution, and the water-oil volume ratio was adjusted, and a high-speed emulsifier (rotation speed of 3000rpm) was used to emulsify for 5 minutes to prepare a Pickering emulsion; the GO concentration in the Pickering emulsion was 2.5mg / mL, the mass ratio of GO to PDMS prepolymer was 1:64, the mass ratio of GO to Span60 was 5:1, and the water-oil volume ratio was 4:1;
[0067] After stirring, the Pickering emulsion is loaded into a mold and placed in a -20°C refrigerator for freezing for more than 5 hours; the frozen Pickering emulsion is then placed in a freeze dryer for drying for more than 24 hours to remove water and cyclohexane; the dried sample is then taken out and cured at 150°C for 30 minutes to obtain a graphene oxide / PDMS composite aerogel; the thermally cured aerogel is further reduced using hydrazine hydrate vapor at 150°C for 5 hours to obtain a graphene / PDMS composite aerogel.
[0068] The density of the graphene / PDMS composite aerogel obtained in Example 5 is about 98.5 mg / cm 3 , modulus is 9.23 kPa, water contact angle is 143.8°, and stress at 50% strain is 5.8 kPa; in addition, the isotropy of the internal structure leads to mechanical isotropy, with the same modulus of 9.23 kPa (error ±0.2 kPa) in the X, Y, and Z directions.
[0069] Example 6
[0070] PDMS and Span60 were added to cyclohexane to prepare a PDMS prepolymer solution; then a certain concentration of graphene oxide dispersion was added to the PDMS prepolymer solution, and the water-oil volume ratio was adjusted, and a high-speed emulsifier (rotation speed was 3000rpm) was used to emulsify for 5 minutes to prepare a Pickering emulsion; the GO concentration in the Pickering emulsion was 2.5mg / mL, the mass ratio of GO to PDMS prepolymer was 1:16, the mass ratio of GO to Span60 was 5:1, and the water-oil volume ratio was 4:1;
[0071] After stirring, the Pickering emulsion was loaded into a mold and placed in a -20°C refrigerator for freezing for more than 5 hours; the frozen Pickering emulsion was then placed in a freeze dryer for drying for more than 24 hours to remove water and cyclohexane; the dried sample was then taken out and cured at 150°C for 30 minutes to obtain a graphene oxide / PDMS composite aerogel.
[0072] The density of the graphene oxide / PDMS composite aerogel obtained in Example 6 is about 60 mg / cm3 , modulus is 6.47 kPa, water contact angle is 140°, and stress at 50% strain is 3.1 kPa; in addition, the isotropy of the internal structure leads to mechanical isotropy, with the same modulus of 6.47 kPa (error ±0.2 kPa) in the X, Y, and Z directions.
[0073] Performance Testing
[0074] The fatigue resistance and cyclic stability of the graphene / PDMS composite aerogel prepared in Example 1 were tested under large strain. The results are shown in Figure 4 As shown, Figure 4 The stress and the error between stress (the difference between stress and average stress) of composite aerogels under 50% strain vary with the number of compression cycles. Figure 4 It can be seen that the graphene / PDMS composite aerogel has good anti-fatigue performance.
[0075] Figure 5 The stress-strain curves of the graphene / PDMS composite aerogel prepared in Example 1 at 10%, 30%, 50%, 70% and 97.5% strain are 0.85 kPa / 1.54 kPa / 3.2 kPa / 12.3 kPa, respectively, wherein the maximum stress can reach 1.7 MPa.
[0076] The graphene / PDMS composite aerogel prepared in Example 1 was subjected to three-dimensional (X, Y, Z) compression and non-equilibrium compression. Figure 6 The experimental results of three-dimensional (X, Y, Z) compression and non-equilibrium compression of graphene / PDMS composite aerogel are given. Figure 6 (a) to (f) are respectively the stress-strain diagram of compression in the X direction, the stress-strain diagram of compression in the Y direction, the stress-strain diagram of compression in the Z direction, the scanning electron microscope diagram of compression in the X direction, the scanning electron microscope diagram of compression in the Y direction, the scanning electron microscope diagram of compression in the Z direction, the stress-strain diagram of oblique compression, the stress-strain diagram of transverse compression, and the stress-strain diagram of half-side compression. Figure 6 It can be seen that the graphene / PDMS composite aerogel exhibits good flexibility and compression resilience.
[0077] The graphene / PDMS composite aerogel prepared in Example 1 was processed into different shapes by blade cutting, such as Figure 7 As shown, the graphene / PDMS composite aerogel exhibits good processing properties.
[0078] The graphene oxide / PDMS composite aerogel prepared by Example 6 was subjected to compression tests at different strains (10%, 30%, 50%, 70%, 90%). The results are shown in Figure 8As shown, it can be seen that the graphene oxide / PDMS composite aerogel can withstand 90% large strain compression and can fully recover.
[0079] The thermal stability of the graphene / PDMS composite aerogels and graphene (GA) and PDMS prepared in Examples 1 to 5 was tested, and the test results are shown in Fig. 9 , Fig. 9 PGA-1 to PGA-5 in the above-mentioned examples correspond to the graphene oxide / PDMS composite aerogels prepared in Example 2, Example 3, Example 1, Example 4, and Example 5, respectively. Fig. 9 It can be shown that the introduction of PDMS in the composite aerogel does not reduce the thermal stability of graphene.
[0080] It can be seen from the above examples that the graphene / PDMS composite aerogel prepared by the present invention has excellent mechanical properties, hydrophobicity and processability.
[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a graphene / polydimethylsiloxane composite aerogel, characterized in that: The following steps are involved: Mixing a polydimethylsiloxane prepolymer, a curing agent, an emulsifier and an organic solvent to obtain a polydimethylsiloxane prepolymer solution; The graphene oxide aqueous dispersion and the polydimethylsiloxane prepolymer solution are mixed and emulsified to obtain an oil-in-water Pickering emulsion; The oil-in-water Pickering emulsion is subjected to random freezing, freeze drying and thermal curing in sequence to obtain a graphene oxide / polydimethylsiloxane composite aerogel; The graphene oxide / polydimethylsiloxane composite aerogel is reduced to obtain the graphene / polydimethylsiloxane composite aerogel.
2. The preparation method according to claim 1, characterized in that: The emulsifier is a Span series emulsifier; the organic solvent includes one or more of cyclohexane, toluene, dichloromethane, chloroform and n-hexane.
3. The preparation method according to claim 1, characterized in that: The volume ratio of the graphene oxide aqueous dispersion to the polydimethylsiloxane prepolymer solution is 10:1 to 1:5; the mass concentration of the graphene oxide aqueous dispersion is 0.1 to 5%; the mass ratio of graphene oxide to polydimethylsiloxane prepolymer in the graphene oxide aqueous dispersion is 1:1 to 1:100; the mass ratio of graphene oxide to emulsifier in the graphene oxide aqueous dispersion is 1:0.1 to 1:
5.
4. The preparation method according to claim 1, characterized in that: The emulsification is carried out in a high-speed emulsifier, the rotation speed of the emulsification is 500 to 9000 rpm, and the time is 3 to 15 minutes.
5. The preparation method according to claim 1, characterized in that: The temperature of the non-directional freezing is -10 to -200°C, and the time is more than 5 hours.
6. The preparation method according to claim 1, characterized in that: The freeze-drying temperature is 0 to -80°C, and the freeze-drying time is more than 24 hours.
7. The preparation method according to claim 1, characterized in that: The thermal curing temperature is 20 to 250° C. and the curing time is 0.1 to 48 hours.
8. The preparation method according to claim 1, characterized in that: The reduction is carried out in the presence of a reducing agent, which includes one or more of hydrazine hydrate, sodium borohydride, ethylenediamine, ascorbic acid and thiourea dioxide; the reduction temperature is 20-200° C. and the time is 0.5-24 hours.
9. The graphene / polydimethylsiloxane composite aerogel prepared by the preparation method according to any one of claims 1 to 8, wherein the graphene / polydimethylsiloxane composite aerogel has isotropy.
10. Application of the graphene / polydimethylsiloxane composite aerogel according to claim 9 in the fields of flexible sensor devices and oil-water separation.
Citation Information
Patent Citations
Preparation process and application of polydimethylsiloxane / graphene oxide porous composite material
CN108484967A
Carbon aerogel material as well as preparation method and application thereof
CN113120879A